The Pauline epistles - Hiebert, David Edmond; (1910-1995) (U.S.A., 2002)
This is a detailed introduction to all of Paul's writings - epistles that without question are among the most precious treasures of the Christian church. Dr. Hiebert discusses the historical circumstances of their writing, deals with ethical problems, and provides helpful general information on the content and nature of the books themselves. Discussed in general and separately, these epistles are treated in chronological order, with emphasis on their eschatology, soteriology, Christology, or ecclesiology.
Keywords: Bible -- New Testament -- Introductions